Regional Cerebral Perfusion and Cerebrovascular Reactivity in Elderly Controls With Subtle Cognitive Deficits - van der Thiel, Merel; Rodriguez, Cristelle; Van De Ville, Dimitri; Giannakopoulos, Panteleimon; Haller, Sven (Frontiers in Aging Neuroscience, 2019)
Background: Recent studies suggested that arterial spin labelling (ASL)-based measures of cerebral blood flow (CBF) as well as cerebral vasoreactivity to CO2 (CVR CO2) show significant alterations mainly in posterior neocortical areas both in mild cognitive impairment (MCI) and Alzheimer disease. It remains, however, unknown whether similar changes occur in at risk healthy elders without clinically overt symptoms. This longitudinal study investigated patterns of ASL perfusion and CVR CO2 as a function of the cognitive trajectories in asymptomatic elderly individuals. Methods: 79 community-dwelling subjects (mean age: 78.7 years, 34 male) underwent three neuropsychological assessments during a subsequent 3-year period. Individuals were classified as stable-stable (SS), variable (V) or progressive-progressive (PP). Between-group comparisons were conducted for ASL CBF and transit-time delay maps and -maps of CO2 response. Spearman’s rho maps assessed the correlation between ASL (respectively CVR CO2 measures) and Shapes test for working memory, as well as Verbal fluency test for executive functions. Three group-with-continuous-covariate-interaction designs were implemented to investigate group-based differences on the association between neuropsychological scores and ASL or CO2 measures. Results: Comparison of CBF maps demonstrates significantly lower perfusion in the V-group as to PP-cases predominantly in parietal regions, including the precuneus and, to a lesser degree, in temporal and frontal cortex. A stronger CVR CO2 response was found in the PP-group in left parietal areas compared to the V-group. V-cases showed a stronger ASL-Shape value relationship than V-group in right temporo-parietal junction and superior parietal lobule. CO2-Shape value correlation was significantly higher in both SS and PP-groups compared to the V-group in right insular and superior perisylvian regions. Conclusions: Our data indicate the presence of decreased ASL and CVR CO2 values mainly in parietal and fronto-temporal areas in cases with the first signs of cognitive instability (V-group). Importantly, the PP-group, at high risk for MCI transition, displays an increase of both parameters in the same areas. Clinicoradiologic correlations also indicate a clear distinction between the V-group and both PP and SS-cases. These data imply the presence of an inverted U-shape pattern of regional blood flow and CVR in old age that might predict subsequent cognitive fate.